Effects of Seagrass Vegetation on Wave Runup Reduction – A Laboratory Study. Issue 1 (1st September 2022) - Manousakas, N; Salauddin, M; Pearson, J; Denissenko, P; Williams, H; Abolfathi, S
Abstract: Increased intensity of extreme climatic events and natural hazards, combined with sea level rise due to global warming, has increased the vulnerability of nearshore and coastal regions to extreme flooding and erosion. The existing hard-engineered infrastructures for flood protection are mainly built from concrete with very high carbon emissions throughout their life cycle. In recent years, the application of nature-based solutions to tackle adverse climatic events has received attention. Nearshore vegetations such as salt marshes and mangroves have proven to attenuate incoming wave energy, thereby reducing wave runup and overtopping at coastal defences. The effectiveness of seagrass vegetation on wave runup attenuation remains less studied. The aim of this physical modelling study was to investigate the performance of prototype seagrass vegetations on wave runup reductions, for a wide range of wave conditions. Results of this study showed that the seagrass vegetation was effective in reducing wave runup on a 'bare' beach. It was found that the location of the vegetation patch within the surfzone and inner-surf zone can play a key role in wave energy dampening. The vegetation type, and packing density also play a significant role in determining the effectiveness of seagrass in wave energy mitigation.